COMPOSITION AND QUALITY OF FRESHWATER LAKE SEDIMENTS (BALVU AND PĒRKONU LAKES) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
Water quality, watershed basin and urbanization are key factors from the perspective of freshwater management; however, actual depth of waterbodies is often an overlooked element. Actual depth represents the overall depth of lake bed and depth of sediments. Some cases have been reported, where with increase of average depth of lake, it is possible to expect improvements of water quality when sediments are removed. If lakes are eutrophic, shallow, overgrown with macrophytes and contain high concentrations of biogenic elements water and lake ecosystem quality can be endangered. Removal of sediments can be an expensive procedure and also depends on the composition, structure, local conditions and total amount of sediments, also the disposal or possible use of sediments must be considered. Therefore, it is crucial to understand not only the genesis of sediments, but also possible pollutants, especially in urban territories. Two lakes in Latvia, where the coastal areas of lakes are urbanized at different levels, were studied. Lake Pērkonu was less affected from urbanization than Lake Balvu, cumulative effects of sedimentation and eutrophication were shown as these two lakes are interconnected. Characterization of lake sediments was done, including measurements of pH, ash content, analysis of C/N ratio, biological composition, metals, polyaromatic hydrocarbons (PAH), content of organic matter and concentration of humic acids. Results show that structure and composition of sediments in studied lakes differ with increasing depth, giving opportunity to track environmental changes in the past and differentiate possible applications of sediments. In deeper layers sediments were mostly formed from algae, but in more recent stages of lake development macrophytes were more dominant. Sediments formed after Ice-Age and located close to the bottom of the lake differ from conditions on paste (relief of lake bed, streams etc.), because areas with accumulated clay material and areas with sandy material were present.